Optimization on biodistribution and antitumor activity of tripterine using polymeric nanoparticles through RES saturation - Juntao Yin; Peiqing Wang; Yuyun Yin; Yantao Hou; Xiaoyong Song (Taylor & Francis Group, 2017)
Systemic delivery of tripterine (TPR) is challenged by its insoluble property and unsuitable pharmacokinetics. This work aimed to develop polymeric nanoparticles (NPs) combined with the reticuloendothelial system (RES) saturation to improve the in vivo distribution and antitumor activity of TPR. TPR-loaded nanoparticles (TPR-NPs) were prepared by the low-energy emulsification/evaporation method and characterized with particle size, entrapment efficiency, and morphology. The resulting TPR-NPs were 75 nm around in particle size and displayed a sustained drug release in pH 7.4 medium. Pharmacokinetic studies revealed that TPR-NPs had the advantage in bettering the pharmacokinetic properties of TPR over the solution formulation. However, the ameliorative effect on pharmacokinetics was more significant in the case of RES saturation (i.e. preinjection of blank NPs). Preinjection of blank NPs followed by injection of TPR-NPs resulted in higher distribution of TPR into the tumor due to reduced sequestration of TPR-NPs by RES. In tumor-bearing mice (prostatic cancer model), TPR-NPs treatment with RES saturation exhibited a superior antitumor efficacy to free TPR and TPR-NPs alone. It can be concluded that formulating TPR into polymeric NPs in combination with RES saturation is an effective means to address the systemic delivery of TPR.